1997
DOI: 10.2169/internalmedicine.36.293
|View full text |Cite
|
Sign up to set email alerts
|

A Candidate Case for Lymphocytic Infundibulo-Neurohypophysitis Mimicking a Neurohypophysial Tumor.

Abstract: A 56-year-old Japanese man presented with a 2-month duration of polyuria and polydipsia. The diagnosis of diabetes insipidus was confirmed by water deprivation and vasopressin injection. The secretory function of the adenohypophysis was estimated as normal by a variety of provocative tests. Magnetic resonance imaging (MRI) displayed the loss of the hyperintense signal of the neurohypophysis and a tumor-like lesion confined to the neurohypophysis. Thetissue specimen resected at transsphenoidal surgery showeddif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Granulomatous lesions of the pituitary gland may be caused by inflammatory reaction originating from a tumor or meningitis. 2,19,29) Therefore, many causes of inflammatory hypophysitis are subsumed under lymphocytic hypophysitis 9,12,13,17,27) and granulomatous hypophysitis. 6,20) Five cases of inflammatory anterior pituitary lesions due to craniopharyngioma and prolactinoma suggested that this entity can be differentiated from lymphocytic and granulomatous hypophysitis.…”
Section: Introductionmentioning
confidence: 99%
“…Granulomatous lesions of the pituitary gland may be caused by inflammatory reaction originating from a tumor or meningitis. 2,19,29) Therefore, many causes of inflammatory hypophysitis are subsumed under lymphocytic hypophysitis 9,12,13,17,27) and granulomatous hypophysitis. 6,20) Five cases of inflammatory anterior pituitary lesions due to craniopharyngioma and prolactinoma suggested that this entity can be differentiated from lymphocytic and granulomatous hypophysitis.…”
Section: Introductionmentioning
confidence: 99%